RESEARCH MODEL OF COMPETITIVENESS OF VIETNAM’S FURNITURE ENTERPRISES - Xuan Thon, Vu; Phan Thiet, Nguyen; Thi Xuan Huong, Nguyen (Journal of Forestry Science and Technology, 2017)
When establishing research model, in addition to the theoretical basis, the model must also rely on actual production. Because there is no common model for all manufacturing sectors, each sector, depending on its own characteristics, adds or eliminates some factors to the overall model and creates the appropriate model of research. Thus, the new research model is likely to be suitable for practice. Based on theories and research on competitiveness in general, as well as the competitiveness of furniture enterprises in particular, such as: Common materials, stable markets, diversified machinery and equipment, low investment capital, etc., to develop a research model on competitiveness of Vietnamese furniture enterprises (VFEs). These results will help researchers identify the type of data to be collected, avoid unnecessary data collection, and time and trouble processing information. At the same time, is the basis for data analysis, explaining the meaning of each type of data.